The Black Civil War soldiers of Illinois : the story of the Twenty-Ninth U.S. Colored Infantry - Miller, Edward A., 1927-2001 (University of South Carolina Press, 1998)
He recounts the unit's role in the final campaign against the Army of Northern Virginia; its final, needless mission to the Texas border; the tragic postwar fate of most of its officers; and the continued discrimination and economic hardship endured after the war by the soldiers.